Biosorption of coloured wastewater onto citric acid modified casuarina equisetifolia leaves powder - Fatma Binti Abd Karim, Siti; Syahirah Binti Abd Kahar, Nurul; Kalthum Ibrahim, Ummi; Adawiyah Abdol Aziz, Rabiatul (International Journal of Engineering and Technology, 2018)
Biosorption is a process that utilizes dead or living biomass and particularly useful for the removal of industrial contaminants. Pine needle (Casuarina Equisetifolia) leaves are an agriculture waste material and can be found abundantly in Malaysia and all over the world. The objectives of this research are to prepare the untreated and treated biosorbent from Casuarina Equisetifolia leaves and to determine the effect of pH, dosage of biosorbent, contact time and initial concentration of the solution to the colour removal. The feasibility potential of treated Casuarina Equisetifolia leaves powder is studied by using a batch mode method that investigates the pH, dosage of biosorbent, contact time and initial concentration of the solution to the colour removal. Samples were analyzed using UV-Visible Spectrophotometer (UV-Vis), Fourier Transform Infra-Red Spectroscopy (FTIR) and Scanning Electron Microscope (SEM) to determine the biosorption capacity. It was observed that treated Casuarina Equisetifolia leaves powder able to achieve 99.72% of colour removal efficiency at optimum condition where pH is 6, dosage of biosorbent is 1.0 g, contact time is 60 minutes and initial concentration of the solution is 10 ppm. This research also observed that treated Casuarina Equisetifolia leaves powder results in an attractive alternative for removing colour that shows a great reduction of coloured wastewater.Â Â